Expanded DMPK repeats in dizygotic twins referred for diagnosis of autism versus absence of expanded DMPK repeats at screening of 330 children with autism - Musova Z (Dove Medical Press, 2016)
Zuzana Musova,1 Miroslava Hancarova,1 Marketa Havlovicova,1 Radka Pourova,1 Michal Hrdlicka,2 Josef Kraus,3 Marie Trkova,4 David Stejskal,4 Zdenek Sedlacek1 1Department of Biology and Medical Genetics, 2Department of Child Psychiatry, 3Department of Child Neurology, Charles University 2nd Faculty of Medicine and University Hospital Motol, 4Gennet, Centre for Fetal Medicine, Prague, Czech Republic Abstract: Myotonic dystrophy type 1 (DM1) belongs to the broad spectrum of genetic disorders associated with autism spectrum disorders (ASD). ASD were reported predominantly in congenital and early childhood forms of DM1. We describe dizygotic twin boys with ASD who were referred for routine laboratory genetic testing and in whom karyotyping, FMR1 gene testing, and single nucleotide polymorphism array analysis yielded negative results. The father of the boys was later diagnosed with suspected DM1, and testing revealed characteristic DMPK gene expansions in his genome as well as in the genomes of both twins and their elder brother, who also suffered from ASD. In accord with previous reports on childhood forms of DM1, our patients showed prominent neuropsychiatric phenotypes characterized especially by hypotonia, developmental and language delay, emotional and affective lability, lowered adaptability, and social withdrawal. The experience with this family and multiple literature reports of ASD in DM1 on the one side but the lack of literature data on the frequency of DMPK gene expansions in ASD patients on the other side prompted us to screen the DMPK gene in a sample of 330 patients with ASD who were first seen by a geneticist before they were 10 years of age, before the muscular weakness, which may signal DM1, usually becomes obvious. The absence of any DMPK gene expansions in this cohort indicates that targeted DMPK gene testing can be recommended only in ASD patients with specific symptoms or family history suggestive of DM1. Keywords: autism, myotonic dystrophy type 1, DMPK gene, genetic testing, comorbidity